Koncepcja fenomenologii życia Anny Teresy Tymienieckiej - Mruszczyk, Magdalena (Autor, 2016)
Анна Тереса Тыменецкая (1923–2014) – польская философ, чья научная деятельность развивалась на рубеже XX и XXI веков. Больше сорока лет она развивала и совершенствовала собственную концепцию феноменологии жизни. Её вдохновляли все дисциплины науки, с которыми она одновременно полемизировала. Особенно важна была для неё феноменология Эдмунда Гуссерля, а также естественные науки. Она считала феноменологию естественным способом отношения человека к действительности и к своей жизни. Естественные науки были для неё источником большой правды о естественном генезисе человеческой жизни. Поэтому феноменология жизни признает эту правду, одновременно предоставляя естественным наукам недостающее им критическое отношение.

Anna Teresa Tymieniecka (1923–2014) – a polish philosopher acting at the turn of the XX and XXI century. She has been developing and perfecting her own conception of phenomenology of life for more than forty years. She was inspired by all disciplines of science with which she also rolled the polemic. Particularly important for her was the Edmund Husserl’s phenomenology and the natural sciences. She recognized this phenomenology as a human’s natural way of relating to the reality and to the human’s life. The natural sciences were a great source of the truth for her about the natural origins of human’s life. The phenomenology of life accepts this truth and provides a missing critical attitude into the natural sciences.
Концепция феноменологии жизни Анны Тересы Тыменецкой
Keywords: феноменология жизни; логос жизни; жизнь; естественные науки; fenomenologia życia; logos życia; życie; nauki przyrodnicze; phenomenology of life; logos of life; life; natural sciences